2009
DOI: 10.2478/v10163-010-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Cystic Tumours with Mesenchymal Stroma

Abstract: Biliary Cystic Tumours with Mesenchymal Stroma Biliary cystadenoma and cystadenocarcinoma are rare cystic liver tumours arising from the bile ducts proximal to the hilum of the liver. The tumours have unique structure with ovarian-type mesenchymal stroma, leading to challenging considerations about their pathogenesis. The differential diagnosis is wide and further complicated by the lack of awareness about these neoplastic processes due to the rarity of the disease. Radical surgical treatment ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Additionally, the morphology of embryonic peritoneum in this specific location is characterized by activated cells that might reveal an evidence of relationship between gonads and developing liver, biliary tree and pancreas (16). These ectopic ovarian deposits might develop the tumors known as BMCNs by stimulating the proliferation of adjacent biliary or pancreatic ducts (18).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the morphology of embryonic peritoneum in this specific location is characterized by activated cells that might reveal an evidence of relationship between gonads and developing liver, biliary tree and pancreas (16). These ectopic ovarian deposits might develop the tumors known as BMCNs by stimulating the proliferation of adjacent biliary or pancreatic ducts (18).…”
Section: Discussionmentioning
confidence: 97%
“…Only few cases of patients with BMCNs who were treated with chemoradiotherapy, have been described (15,24). In 2009, Vanags et al (18) reported the beneficial impact of systemic 5-fluoruracil-based chemotherapy in a patient diagnosed with recurrent and metastatic disease 41 months after the surgical resection of an invasive BMCN. In another case, as the patient was not candidate for major hepatectomy, hepatic arterial infusion of cisplatin was used (28).…”
Section: Discussionmentioning
confidence: 99%
“…"Central dot" sign is observed by CT. Bridges across the cavities are evident by MRI. Both these findings represent branches of portal vein embedded in connective tissue strands adjacent to and surrounded by dilated bile ducts [28].…”
Section: Radiological Findings and Differential Diagnosismentioning
confidence: 96%
“…Topics in the Surgery of the Biliary Tree gland and retroperitoneal space showing similar stroma [27]. During embryogenesis, ectopic ovarian rests might develop in the liver, along biliary tree, in the pancreas or retroperitoneal tissues and stimulate the proliferation of adjacent biliary or pancreatic ducts by synthesis of growth factors [9,28]. Indeed, during embryonic development, gonads initially are located directly under the diaphragm, dorsally to the liver and pancreatic tail, and only later they descend to the typical anatomic location seen in adults.…”
Section: Gender: Proportion Of Female Patientsmentioning
confidence: 99%
See 1 more Smart Citation